Tissue-specific and differentiation-specific expression of a human K14 keratin gene in transgenic mice. - Vassar, R (1989)
A construct containing approximately 2500 base pairs (bp) of 5' upstream and approximately 700 bp of 3' downstream sequence was used to drive the expression of an intronless human K14 gene in vitro and in vivo. To track the expression of the gene, a small sequence encoding the antigenic portion of neuropeptide substance P was inserted in frame 5' to the TGA translation stop codon of the gene. Surprisingly, this gene was expressed promiscuously in a wide variety of cultured cells transiently transfected with the construct. In contrast, when introduced into the germ line of transgenic mice, the construct was expressed in a fashion analogous to the endogenous K14 gene--namely, in the basal layer of stratified squamous epithelia. Our results suggest that some regulatory mechanism is overridden as a consequence of transient transfection but that sequences that can control proper K14 expression are present in the construct. The appropriate tissue-specific and differentiation-specific expression of K14.P in transgenic mice is an important first step in characterizing a promoter that could be employed to drive the foreign expression of drug-related genes in the epidermis of skin grafts.